Differential susceptibility effects of the 5-HTTLPR and MAOA genotypes on decision making under risk in the Iowa gambling task - Rehn, Mattias; Nilsson, Kent W.; Hultman, Cathrine; Vadlin, Sofia; Åslund, Cecilia (Frontiers in Psychiatry, 2025)
IntroductionThe interplay between genetic and environmental factors, as explored through studies of gene-environment interactions (cG×E), has illuminated the complex dynamics influencing behavior and cognition, including decision-making processes. In this study, we investigated the differential susceptibility effects of the 5-HTTLPR and MAOA genotypes on decision-making under risk using the Iowa Gambling Task.MethodsData from 264 participants (138 women, 126 men) aged 18-22 years, from the 2015 wave of the Survey of Adolescent Life in Västmanland (SALVe Cohort) was analyzed. Participants provided genetic data including the MAOA and 5-HTTLPR genotypes, and completed the Iowa Gambling Task (IGT) to evaluate decision-making behavior. Parent reports, including assessments of positive parenting styles and early life stress were used for cG×E analysis.ResultsIn a General Linear Model, significant interactions were found among males for the 5-HTTLPR, with SS/SL carriers showing higher net scores with positive parenting and lower scores with less positive parenting in relation to decision-making under risk in the IGT (trials 61-100), indicating differential susceptibility effects. Male LL carriers showed minimal fluctuation in IGT scores. Similar effects were observed for males with the MAOA S-allele. No significant interactions were found for females.DiscussionIn conclusion, our study indicates that the 5-HTTLPR and MAOA genes demonstrate susceptibility to environmental factors in influencing decision-making under risk among males, as assessed by the Iowa Gambling Task. We anticipate that these findings will contribute to advancing the understanding of the complex interactions between genetic and environmental factors in shaping human behavior and decision-making.